2015
DOI: 10.1371/journal.pone.0135859
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Derived Peptides for Detection of Ebola Virus Glycoprotein

Abstract: BackgroundCurrent Ebola virus (EBOV) detection methods are costly and impractical for epidemic scenarios. Different immune-based assays have been reported for the detection and quantification of Ebola virus (EBOV) proteins. In particular, several monoclonal antibodies (mAbs) have been described that bind the capsid glycoprotein (GP) of EBOV GP. However, the currently available platforms for the design and production of full-length mAbs are cumbersome and costly. The use of antibody fragments, rather than full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Binding analysis of solubilized and refolded scFv and VHH antibodies were performed by direct ELISA using 96 well fat bottom polystyrene plates. The commercially available recombinant version of the capsid glycoprotein (GP) of Ebola GP [29] and human serum albumin (HSA) were coated with equimolar amounts at 4 • C overnight. The unbound protein samples were washed with PBST buffer (PBS with 0.05% Tween 20), and the untenanted spaces were blocked with 3% (w/v) non-fat skim milk dissolved in PBS.…”
Section: Elisa Analysis Of Antibody Binding To Target Antigensmentioning
confidence: 99%
“…Binding analysis of solubilized and refolded scFv and VHH antibodies were performed by direct ELISA using 96 well fat bottom polystyrene plates. The commercially available recombinant version of the capsid glycoprotein (GP) of Ebola GP [29] and human serum albumin (HSA) were coated with equimolar amounts at 4 • C overnight. The unbound protein samples were washed with PBST buffer (PBS with 0.05% Tween 20), and the untenanted spaces were blocked with 3% (w/v) non-fat skim milk dissolved in PBS.…”
Section: Elisa Analysis Of Antibody Binding To Target Antigensmentioning
confidence: 99%
“…7). Rodríguez-Martínez et al [23] reported that the scFv-13C6 mAb exhibited the highest EBOV GP-binding activity, followed by scFv-13F6 and Fab-KZ52 in ELISA experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibody fragments to neutralize viruses or prevent virus infection is not novel; proof of concept experiments have shown their potential applications in the context of different viral infections such us HIV (Lülf et al, 2014), Influenza A H1N5 (Bal et al, 2015), SARS (Sui et al, 2004), HPV (Culp et al, 2007), and West Nile virus (Gould et al, 2005). A recent contribution by Rodríguez-Martínez et al (2015) offers proof-of-principle of the application of three anti-EBOV mAb fragments, containing the variable regions the mAbs KZ52, 13C6, and 13F6, in immunological assays to specifically detect recombinant GP.…”
Section: Bottlenecks In Anti-ebola Mab Production: Scaling Up Cost mentioning
confidence: 99%